Матеріали до Словника концептуальної / ідеографічної організації назв суб'єктів культурної діяльності (термінографічна когнітосфера культури та мистецтва) - Лозова, Н.Г. (Лексикографічний бюлетень, 2013)
Conceptual / іdeographical arrangement of the names of subjects of cultural activity according to five conceptualization level in the cognitosphere of culture and art are examined in the Terminological Dictionary materials. Key words: ideographical arrangement, subjects of cultural activity, conceptualization level.